Exploration of Medicine 2020
DOI: 10.37349/emed.2020.00004
|View full text |Cite
|
Sign up to set email alerts
|

PNPLA3 gene and kidney disease

Abstract: Chronic kidney disease (CKD) is a disease regularly seen in clinical practice. At present, CKD is described as a change of kidney structure and/or function and it is classified in relation to cause, values of glomerular filtration rate and albuminuria category. Seeing that CKD is closely linked to the development of end-stage renal disease and other comorbidities, the determination of additional independent predictors for CKD is clinically necessary. At present, there is evidence associating non-alcoholic fatt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
16
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 48 publications
(147 reference statements)
0
16
0
1
Order By: Relevance
“…The participation of adiponutrin in energy metabolism, triglyceride lipolysis and other metabolic processes has been proven earlier and presented in publications of previous years exclusively within the framework of liver pathology: non-alcoholic fatty liver disease with the risk of coronary heart disease [13], with the risk of chronic kidney disease [14], but data of clinical and experimental studies regarding adiponutrin blood serum level determination in patients with hypertension are very few, and there are almost no scientific data in comorbidity with obesity. Therefore, the study of ADPN -the marker of metabolic disorders to determine the character of the flow of HT in comorbidity with obesity is actually today.…”
Section: Introductionmentioning
confidence: 89%
“…The participation of adiponutrin in energy metabolism, triglyceride lipolysis and other metabolic processes has been proven earlier and presented in publications of previous years exclusively within the framework of liver pathology: non-alcoholic fatty liver disease with the risk of coronary heart disease [13], with the risk of chronic kidney disease [14], but data of clinical and experimental studies regarding adiponutrin blood serum level determination in patients with hypertension are very few, and there are almost no scientific data in comorbidity with obesity. Therefore, the study of ADPN -the marker of metabolic disorders to determine the character of the flow of HT in comorbidity with obesity is actually today.…”
Section: Introductionmentioning
confidence: 89%
“…Although several studies have shed light on the pathogenesis of DN, several aspects of its condition remain unclear; thus, further comprehensive investigations and evidence-based findings are needed to elucidate the mechanism underlying disease progression ( Mantovani and Zusi, 2020 ; Miao et al, 2021a ). Cadmium (Cd), a transition metal that is, toxic by nature and an environmental pollutant, is generated from industrial sources and found in air, water, food, and cigarette smoke.…”
Section: Introductionmentioning
confidence: 99%
“…A variety of pathophysiological principles is shared by many fibrotic-associated diseases, such as cirrhosis, kidney fibrosis, myocardial fibrosis, and idiopathic pulmonary fibrosis ( Miao et al, 2021a ). Fibrotic diseases are estimated to account for up to 50% of deaths in the developed world ( Mantovani and Zusi, 2020 ).…”
Section: Introductionmentioning
confidence: 99%